Design and Development of an Online Queue Administration System in Health Services (Study Case: Klinik Halyna Pageruyung Kendal) - Arif Fitra Setyawan; Amelia Devi Putri Ariyanto; Ari Dina Permana Citra (ProBisnis : Jurnal Manajemen, 2023)
Queuing culture reflects the identity of an advanced nation, because it forms a social attitude that is disciplined and respects other people. Apart from respecting each other, queuing in an orderly manner and not overtaking or breaking through the queue includes respecting the rights of others. Online queuing systems offer many benefits, including elimination of queues, increased efficiency in service delivery, and increased customer satisfaction. They can be applied to a wide range of industries, including healthcare, banking, retail and government services. In a health service agency such as a clinic, service for customer satisfaction is very important, so efforts are always made to improve service quality. An online queuing system is a digital system that allows users to enter a virtual queue, where they wait their turn to access services or receive assistance. The system provides users with a way to book time slots, secure their place in the queue, and receive real-time updates on the status of their positions. To implement an online queuing system requires investment in appropriate hardware and software, such as a cloud-based queue management system or mobile application. Overall, online queuing systems can help optimize service delivery, reduce waiting times, and improve the overall customer experience. The existence of a queuing system makes it easy for people to manage time efficiently. The increasing need for fast services requires that every public service, especially health clinics, have a queuing system. With the Online Queue Administration System to help queue administration problems.